A geometria no ensino da probabilidade - Bispo, David Marques (2018)
The study on the history of probability and geometric probability has been little disseminated on the national scene. There is a shortage of scientific papers that address these two issues, often the likelihood is synonymous with "gambling." This work will focus on the geometric probability presenting and discussing problems of a continuous nature related to lengths of straight segments, areas of flat figures or volumes of solids. In the paper was presented a historical retrospective of the mathematicians who contributed to the development of probability and then a study on probability to have a theoretical basis for the main purpose of the dissertation which is to show the applications of Probability in the field of Geometry. The work will be developed based on the bibliographical research, which consists of the description of the characteristics in studies that recover the scientific knowledge. The problems that will be proposed and worked, although they are classic problems of Geometric Probability, are almost always unknown by many elementary and high school teachers and also by the absolute majority of the students that are at this level of schooling. It is intended, therefore, to work concepts of geometric probability through the applications. The proposed theme contributed to the improvement of mathematical knowledge and also presented a differentiated methodological dynamics for Probability teaching, since this topic is not much explored in Basic Education.